ИННОВАЦИОН РАҲБАР ИЖТИМОИЙ – ПСИХОЛОГИК ФЕНОМЕН СИФАТИДА - Нурабуллаев, Т.А. (SCIENCE and SOCIETY, 2021)
The article is devoted to the topic of innovative leadership as a socio-psychological phenomenon. The article also discusses a number of socio-psychological qualities of an innovative leader, innovation and social development, management practice and its effectiveness, daily changes and leadership opportunities, modern leadership initiative, social activity, effective management skills, behavioral strategy through advanced socio-psychological concepts.